PENGARUH DISIPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT CAPELLA MEDAN CABANG PEMATANGSIANTAR - Kurniawan, Ahmad; Lie, Darwin; Efendi, Efendi; Harahap, Kartini (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
The results of this study can be summarized as follows: 1. Employees declare good work discipline, leadership style and employee performance is categorized well. 2. Regression analysis result Ŷ = 19,070 + 0,280 X1 + 0,447X2, meaning there is positive influence between work discipline (X1) and leadership style (X2) on employee performance (Y). 3. Correlation analysis results obtained r value = 0,787, meaning there is moderately and positive correlation between work discipline variables and leadership style with employee performance. Whether or not the performance of employees can be explained coefficient of determination by work discipline and leadership style can be 61,9%. 4. H0 Hypothesis rejected, meaning that work discipline and leadership style have a positive and significant impact on employee performance at PT Capella Medan Branch Pematangsiantar. As for suggestion of this research is to increase the influence of work discipline, hence company have to increase sanction firmly to employees who violate with work discipline regulation which have been applied company. To realize an effective and balanced leadership style, leaders should be able to make their own decisions, and be able to use a good leadership style in accordance with authority as a leader. To improve employee performance that is by giving appeal and training to employees to create the ability to cooperate between leaders, co-workers can run more optimally